PROTOTYPE SISTEM INFORMASI PARIWISATA KABUPATEN WONOGIRI DAN SEKITARNYA DENGAN GOOGLE MAPS - Elysia Putri; Jap Tji Beng; Wasino Wasino (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Tourism is one of the sectors that can be relied upon in economic activity because it has potential, priorities, and generate tremendous income, especially for the areas that have the potential for an extensive tour with objects and tourist services are available such as Wonogiri district. Presentation of tourism information required as a guide for tourists who want to visit. Problems encountered, information about tourism’s wonogiri is still lacking and led to information about the location and routes are limited, so tourists who visit difficult. By using GIS as a tool of geographic analysis, can be developed into a tourist information system that contains a map showing the location of objects and tourist services along with descriptions. Maps are displayed loaded with maps google services. The purpose of this system is to present tourism information system that displays data associated with the presence of the tourist attractions in Wonogiri with google maps. This system helps the tourists to find the location of the attractions that they had never known before, and get information about the tour including hotel facilities, accommodation, restaurants, and routes between the object and tourist services as well as the distance they will go. Key wordsInformation Systems Tourism, Geographic Information Systems, Google Maps, SIP, Tourism,  Wonogiri District